Neighborhood environment perceptions associate with depression levels and cardiovascular risk among middle-aged and older adults: Data from the Washington, DC cardiovascular health and needs assessment. (2nd November 2021) - Andrews, Marcus R.; Ceasar, Joniqua; Tamura, Kosuke; Langerman, Steven D.; Mitchell, Valerie M.; Collins, Billy S.; Baumer, Yvonne; Gutierrez Huerta, Cristhian A.; Dey, Amit K.; Playford, Martin P.; Mehta, Nehal N.; Powell-Wiley, Tiffany M.
Abstract: Objectives: Little is understood about associations between neighborhood characteristics and depression, a cardiovascular disease (CVD) risk factor, in diverse populations. We examined relationships between perceived/objective neighborhood characteristics, depression, and CVD markers within the Washington, DC CV Health/Needs Assessment, an evaluation among predominantly African-American (AA) adults in resource-limited DC communities. Method: Factor analysis of overall neighborhood environment perception (NEP) identified three NEP sub-scores:1) violence; 2) physical/social environment; 3) social cohesion (higher score = more favorable perception). Objective neighborhood characteristics were measured by geospatially-derived scores of walkability, transportation, and crime. Depression was defined by the revised Center for Epidemiologic Studies Depression Scale (CESD-R). We used linear-regression modeling to examine neighborhood measures and CESD-R associations. To investigate a subsequent connection with CVD risk, we examined relationships between CESD-R and CVD-associated cytokines in a population subset. Results: Participants ( N  = 99; mean age = 59.06; 99% AA) had a mean CESD-R score = 5.8(SD = 8.88). In adjusted models, CESD-R scores decreased by 0.20 units ( p  = 0.01) for every overall NEP unit-increase. Perceived physical/social environment (β = −0.34, p  = 0.04) and social cohesion (β = −0.82, p  = 0.01) were related to CESD-R while perceived violence was not (β = −0.28, p  = 0.1). Of objective neighborhood environment measures (i.e. walk, transit, bike, personal crime, and property crime scores), only property crime score was associated with depression (β = 4.99, p  < 0.03). In population subset ( n  = 42), higher CESD-R associated with higher IL-1β (β = 21.25, p  < 0.01) and IL-18 (β = 0.006, p  = 0.01). Conclusion: Favorable neighborhood perceptions are related to lower depressive symptoms in a predominantly AA cohort from Washington, DC resource-limited communities. Neighborhood perceptions appear to be strongly associated with depressive symptoms compared to objective characteristics. Increasing CESD-R scores were related to higher pro-inflammatory markers. Improving neighborhood perceptions may be beneficial to psychological well-being and CV health for urban minority residents.